2002
DOI: 10.1093/brain/awf165
|View full text |Cite
|
Sign up to set email alerts
|

Markers for different glial cell responses in multiple sclerosis: clinical and pathological correlations

Abstract: Disease progression in multiple sclerosis occurs within the interface of glial activation and gliosis. This study aimed to investigate the relationship between biomarkers of different glial cell responses: (i) to disease dynamics and the clinical subtypes of multiple sclerosis; (ii) to disability; and (iii) to cross-validate these findings in a post-mortem study. To address the first goal, 51 patients with multiple sclerosis [20 relapsing remitting (RR), 21 secondary progressive (SP) and 10 primary progressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
173
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(199 citation statements)
references
References 56 publications
18
173
0
Order By: Relevance
“…However gliosis is difficult to quantify by immuncytochemical techniques and usually done by counting cells, and the number and length of extending processes. The finding of grey matter astrogliosis and elevated GFAP levels is in line with previous results from human multiple sclerosis post-mortem tissue [6].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However gliosis is difficult to quantify by immuncytochemical techniques and usually done by counting cells, and the number and length of extending processes. The finding of grey matter astrogliosis and elevated GFAP levels is in line with previous results from human multiple sclerosis post-mortem tissue [6].…”
Section: Discussionsupporting
confidence: 92%
“…In immunocytochemistry, GFAP has been used as a marker for astrogliosis and S100B for activation of astrocytes, ferritin as a marker for microglial activation and neurofilaments (Nf) as a marker for axonal damage [3][4][5][6]. This study examines the potential of ELISA-based methods to assess neurodegeneration in CREAE.…”
mentioning
confidence: 99%
“…This protein has been found in CSF of 13 out of 18 patients with MS, whereas it was undetectable in any of the 11 control patients (19). CSF studies have also found that there is a significant trend for increasing S100β levels from primary progressive (PP) to secondary progressive (SP) to relapsing remitting (RR) MS, and that S100β was significantly higher in RR MS than in control patients, demonstrating that S100β is a good marker for the relapsing phase of the disease (20). S100β immunization and S100β-specific T-cell adoptive transfer can induce EAE and uveoretinitis in the Lewis rat, demonstrating that nonmyelin antigens can have an immunopathogenic role in inflammatory CNS disease (21,22).…”
Section: Introductionmentioning
confidence: 96%
“…The proven benefit common to all currently recommended treatments is a reduction in the rate of clinical relapse, which has been associated to a transient slowing of disease progression [3]. During the early phase of MS active disease has been related to elevated levels of S100B [4] and the nitric oxide metabolites nitrate and nitrite (NO x ) [5].…”
Section: Introductionmentioning
confidence: 99%